2016
DOI: 10.1016/j.urology.2015.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic and Pathologic Characterization of Papillary Architecture in Struvite Stone Formers

Abstract: Objective To describe the endoscopic characteristics of renal papillae in struvite stone formers (SF). Materials and Methods From 2009 to 2014, patients undergoing percutaneous nephrolithotomy were prospectively enrolled in our study. Endoscopic analysis and biopsy of papillae was performed to demonstrate the presence and percentage surface area (SA) of Randall's plaque or ductal plug. Comparison with idiopathic calcium oxalate (CaOx) SF and non-SF controls was performed. Results We identified 29 struvite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The only consistent finding in the struvite group was LC, which may correlate to interstitial inflammation as demonstrated in a recent study [26]. In line with our data, their findings suggest that RP has a limited role for struvite stone formation and an alternate pathogenic mechanism is thus implicated [26].…”
Section: Discussionsupporting
confidence: 91%
“…The only consistent finding in the struvite group was LC, which may correlate to interstitial inflammation as demonstrated in a recent study [26]. In line with our data, their findings suggest that RP has a limited role for struvite stone formation and an alternate pathogenic mechanism is thus implicated [26].…”
Section: Discussionsupporting
confidence: 91%
“…Different from other types of urinary stones, the physicochemical processes that lead to infection stone formation are largely driven by the presence of ureolytic microorganisms in the urinary tract system. randall's plaque has been suggested to have a key role in the lithogenesis of calcium oxalate stones 69 , but seems to have a limited role in struvite stone formation 70 . Indeed, Jaeger et al 70 reported substantially lower levels of Randall's plaque formation in struvite stone formers than in calcium oxalate stone formers.…”
Section: Infection Stone Formationmentioning
confidence: 99%
“…randall's plaque has been suggested to have a key role in the lithogenesis of calcium oxalate stones 69 , but seems to have a limited role in struvite stone formation 70 . Indeed, Jaeger et al 70 reported substantially lower levels of Randall's plaque formation in struvite stone formers than in calcium oxalate stone formers. Owing to the lack of or low abundance of Randall's plaque, the authors suggested that struvite formation is probably independent of the presence of Randall's plaque.…”
Section: Infection Stone Formationmentioning
confidence: 99%
“…Papillary appearance might also provide unique information in instances where the stones are not believed to originate from the papilla. For example, papillary appearance in stone formers that form struvite 34 or uric acid stones 35 is distinct from that of individuals who do not form stones. Currently, our understanding of the clinical significance of papillary abnormalities remains limited, although the advent of high-definition renal endoscopy opens many opportunities for future investigations in this area.…”
Section: Papillary Inspectionmentioning
confidence: 99%